2012
DOI: 10.3109/10715762.2012.724532
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS-K+channel signaling pathway regulated secretion of human pulmonary artery endothelial cells

Abstract: The objective was to investigate the molecular mechanism of mitochondrial reactive oxygen species (ROS) signaling regulation of pulmonary artery endothelial cell (HPAEC) secretion in the condition of oxidative stress. Acrolein (40 μM) induced HPAEC mitochondrial generation of ROS, rotenone (2 μmol/L) blocked mitochondrial respiratory chain complex I, cesium chloride (CsCl, 40 mmol/L)blocked K(+)channels, and saline (0.9 g/dl) were used as control. The generations of NOS, ET-1 and VEGF were determined with ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…production of matrix protein and ROS, activity of K v , expression of HIF and growth factors, segregation of cytokines like endothelin and thromboxane) of vascular cells (i.e. endothelial cells, smooth muscles, adventitial fibroblasts) [6][7][8], while the later tend to focus on structural transformation such as the endothelial lesion, smooth muscle and adventitial fibroblast proliferation which is consistent with former modulation. Besides, the innervation and microenvironment also contribute significantly to the structural remodeling and persistent vasoconstriction of the pulmonary circulation [5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…production of matrix protein and ROS, activity of K v , expression of HIF and growth factors, segregation of cytokines like endothelin and thromboxane) of vascular cells (i.e. endothelial cells, smooth muscles, adventitial fibroblasts) [6][7][8], while the later tend to focus on structural transformation such as the endothelial lesion, smooth muscle and adventitial fibroblast proliferation which is consistent with former modulation. Besides, the innervation and microenvironment also contribute significantly to the structural remodeling and persistent vasoconstriction of the pulmonary circulation [5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 73%
“…The increased ROS could activate and stabilize HIF-1a, and HIF-1a could in turn increase ROS production through its downstream signaling involved the imbalance of the prooxidation and anti-oxidation [20,43,44]; meanwhile, ROS, especially H 2 O 2 , directly suppress the activity of K + channels, and HIF-1a could also downregulate K v 1.5 expression, which both decreases K + currents, and results in membrane depolarization, promoting Ca 2+ influx through VDCC opening, inducing vascular constriction [20,36,45]. Moreover, the ROS-K + signaling pathway modulates NO, ET-1, and VEGF secretion in human pulmonary arterial endothelium under oxidative stress, further affecting the initiation of HPH [6]. Besides, our previous study found in the PH induced by monocrotaline, the activity of telomerase reverse transcriptase (TERT) was increased and TERT promoted the PASMCs proliferation.…”
Section: Stage Ii: the Crucial Course Of Pulmonary Vasoconstriction Amentioning
confidence: 97%
“…The FAM-fluorescence detection was performed with a confocal microscope (excitation wavelength of 495 nm, emission wavelength of 525 nm; Leica, Mannheim, Germany) after transfection efficiency had been reached for 6 h at 37°C in a CO 2 incubator. The cell transfection rate was ~80%, and the transfection process continued for 48 h. Assessment of the various specimens were carried out for RT-PCR and western blot analysis, and the MTT assay of the cell proliferation rate was performed as previously described (24). Each assay was performed in triplicate and independently repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…This leads to mPTP opening and release of mitochondrial superoxide/hydrogen peroxide (Seidlmayer et al , ). Likewise, mitochondrial superoxide/hydrogen peroxide formation was associated with increased ET‐1 secretion of pulmonary artery endothelial cells (Ouyang et al , ).…”
Section: Redox Regulation Of Vascular Function By Oxidative Degradatimentioning
confidence: 99%